THE ADAPTATION OF A DIPLOMAT TO THE TIME OF WARS OF INDEPENDENCE AND LIBERAL REVOLUTION. LUIS DE ONÍS BEFORE THE EXPANSIONISM OF THE UNITED STATES AND THE EMANCIPATION OF IBEROAMÉRICA, 1809-1922 (Tzintzun, Revista de Estudios Históricos, 2022)
Luis de Onís was a “pre-liberal” diplomat, who developed diplomatic activitiesfor forty years both in Europe and America between the Ancien Regime and theliberal Triennium, known above all for the 1819 Treaty with the United States.He is an example of the adaptation of the elites in the transition to thecontemporary age. From sources deposited in the National Historical Archiveand the General Archive of the Indies, it was analyzed its vision of Ibero-Americaand the means proposed to contain its emancipation, highlighting its proposalsof a more radical and realistic character with respect to the generality of theSpanish political class.
Keywords: international relations; Ibero-American Independence; liberal transition; biography; Napoleonic Wars